EXTRACTION AND IDENTIFICATION OF REDUCING SUGARS IN AZANZA GARCKEANA FRUIT - E. KARU; J. MAITALE; F. U. MAIGARI, (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY (2536-6041), 2019)
Azanza garckeana (AG), is a tropical tree widely distributed in Eastern, Southern and Western Africa. The plant species has continued to attract interest due to its cytotoxicity and antioxidant activities. Research on particularly reducing sugars from the plant found in Northern Nigeria remain largely unexploited. Hence, there is a necessity for special research on such compound(s) which could lead to the actual understanding of the medicinal impact of the plant specimen. AG fruit samples were collected from five different areas of Tula town, Gombe state Nigeria and prepared accordingly for sugars analysis. Fehling’s solutions A and B, then chromatography analysis was used to test the presence of reducing sugars. Ethanol extraction method of Benedict’s solution test was applied for reducing sugar test. Fehling’s solutions gave a brick red precipitate indicating the presence of reducing sugars. Orange-brown precipitate was observed from the ethanolic extract solution for reducing sugars test. The compounds extract was found to contain, glucose, mannose, galactose, fructose and sucrose. The functional groups OH, C=O and other absorption bands were identified by IR spectroscopy. Presence of the sugars in the AG fruits confirms its consumption safety and as good source of energy.